Generalization and Extension of Liu,H. and Xu,S. and, Jiandong Wang Results in Cone Metric Spaces Over Banach Algebras for Generalized Lipschitz Conditions - Behera, Gajendra Kumar (Asian Journal of Science, Technology, Engineering, and Art, 2024)
This article aims to present and establish some fixed-point results for a mapping satisfying generalized Lipschitz conditions and appealing to the normality of the cone. Our results extend and generalize several known results from the existing literature.